DINAMIKA KEBUDAYAAN ISLAM MELAYU DI NUSANTARA - Jufri Suyuthi Pulungan (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2017)
The socio-cultural community of Palembang identifies itself as a Malay ethnic group. As a Malay family, Palembang's location is very strategic, so many foreign visitors who visit or settle in Palembang, among them, ethnic Chinese and Arabs and other foreigners. In turn, not a few of these migrants actually settled in Palembang, including, ethnic Chinese (Tionghoa). It is estimated that since the 7th century AD, there has been established trade relations between China and Palembang, although written sources mention that the peak of trade relations occurred in the 10th-16th century AD. On the post trip of Commander Cheng Ho three times to Palembang (1413-1415), Muslims from China flocked to come to Palembang. Lehih far away, Cheng Ho's second coming to Palembang in 1414, carrying 63 ships with 28,560 passengers. Furthermore, referring to the Barnes chronology, in the 13th century AD at least 83,980 Chinese stopped in to Palembang, mostly Muslims, because China was dominated by the Ming Dynasty, a symbol of Muslim rule in China. To commemorate the services of Admiral Cheng Ho in the spread of Islam in Palembang, ethnic Chinese Muslims took the initiative to establish Masjid al-Islam Muhammad Cheng Ho located in Jakabaring. The existence of the Cheng Ho Mosque has brought different colors and shapes with other mosques in the city of Palembang. Cheng Ho Mosque has a specification of architectural form and ornament on Cheng Ho Mosque, both structural and non structural showing the acculturation of Chinese (Islamic), Islamic (Arab), and local culture (Malayan Palembang) elements. The existence of Cheng Ho Mosque Palembang not only serves as a place of worship. But also the place of events of Islamic and civic activities and guidance for mu'alaf, especially derived from ethnic Chinese. Thus, the existence of Cheng Ho Palembang Mosque is not only a place of worship typical of Tionghoa Islam, but also a new portrait of Malayan Malay Islam.Keywords: Cheng Ho Palembang Mosque, Acculturation, and Malay Islam